The relationship between quality of disclosure in corporate annual reports and firm-specific characteristics : the case of NACRA / Nooraisah Katmun@ Katmon and Hafiz-Majdi Ab. Rashid - Katmun@Katmon, Nooraisah; Ab. Rashid, Hafiz-Majdi (Institute of Quality and Knowledge Advancement (InQKA) and University Publication Centre (UPENA), 2007)
This study empirically examined the relationship between firm-specific characteristics and the quality of disclosure of company annual reports in Malaysia. Due to the increasing need of users towards accounting information, a full quality and transparent disclosure must to be provided by companies. As a measurement of quality, I used the NACRA as a benchmark of sound quality of reporting. Firms that won NACRA were considered as firms that provided quality of disclosure in their annual reports. The independent variables tested in this study were firm size, ownership structure, leverage and profitability. The match-paired sample comprises 52, 56 and 66 firms that won and lost NACRA during the years 1999, 2000 and 2001. This study used descriptive statistics, Mann-Whitney U test, Logistic regression and Linear regression (as the test of robustness) to test the hypotheses. Results show that ownership structure is the only variable found to be significant in influencing the level of disclosure by firms in Malaysia. Nevertheless, this study also realizes some limitations like the small number of independent variables tested and the small size of sample.